Global sustainable capitalism - Svigir, Mario; Xia, Harry; Goncalves, Marcus (Economics and public policy collection., 2020)
Sustainable capitalism knowledge is often assumed for exclusive association with information about some forms of environmental crises. When we speak of sustainable and unsustainable, we speak of a systemic crisis of long-term dimension in the economy and business models, on all levels. We talk of local to a global crisis, with detrimental effects on humans and the environment, as well as economic organizations, of various kinds, often forfeiting any economic, social, and environmental future. The long-term crisis is not just a crisis of long-term investment, but also a crisis of human and ecological capital. The authors propose a new conceptual business model, polycentric, at many levels. This research is an attempt to contribute to the global alliance for such sustainable capitalism in the making. In part, this is an ambitious undertaking, as the authors analyzed vital UN documents on sustainable development, as part of what they advocate as sustainable capitalism, as a systemic response to existing shortcomings of the present model. This text attempts to educate global stakeholders about the importance, the rationale, and the pathway to introduce sustainable capitalism into global economics and business models.